Identification Identifikasi Konflik Antara Nelayan, Pengusaha Ikan dan Pemerintah dalam Kegiatan Perikanan Tangkap di TPI PPS Cilacap, Jawa Tengah: Identifikasi Konflik Antara Nelayan, Pengusaha Ikan dan Pemerintah dalam Kegiatan Perikanan Tangkap - Alvian Dwi Vidianto; Naya Distal Awalia Putri; Dinda Devina Putri Wiranti; Syifa Auliya Harsoleh; Cantika Zalsa Nabila; Sabrina Putri Arifiana; Rizka Indah Cahyani; Eva Widyastuti; Alya Sabita Puteri Hendrawan; Tegar Hilmi Syawalandita; Fauzi Surya Nugraha; Jati Suryo Kusumo; Ani Suryanti; Rika Prihati Cahyaning Pertiwi; Lilik Kartika Sari; Muslih; Mahardika Nur Permatasari; Ahmad Naufal Attaqi (Talenta Publisher, 2026)
The capture fisheries sector plays a strategic role in the national economy, including at the Cilacap Ocean Fishing Port (PPS Cilacap), the center of marine product fishing and distribution. This study aims to identify the forms, causes, and impacts of conflicts between fishermen, fish entrepreneurs, and the government in managing capture fisheries at the Cilacap PPS. Data collection was conducted on November 10, 2025, through questionnaire-based interviews with fishermen, entrepreneurs, and port managers, covering operational aspects, economics, regulatory perceptions, and potential conflicts. The results indicate that conflicts are triggered by differences in interests in access to port facilities, catch distribution, understanding of fishing zone regulations, and inequality in asset ownership and capital sources. Visual analysis of the data shows that fishing activities are dominated by medium-scale vessels measuring 5–30 GT, the use of fishing rods as the primary gear, and a high reliance on diesel fuel for operations. Although most fishermen have joined groups, access to government assistance and insurance remains unequal. These findings underscore the need for institutional strengthening, increased regulatory dissemination, and the implementation of collaborative zone-based fisheries management to reduce the potential for conflict and support the sustainability of capture fisheries in the Cilacap Fishing Port (PPS)